Adverse Effects of Climate Change in Bangladesh: its Physiological and Economic Impacts - Jahan, Nusrat (i-Proclaim, 2020)
Rapid changing of climate, the effects of greenhouse and global warming, is an alarming situation of the global map with its adverse effects, sending several countries under the waves. Unfortunately, Bangladesh stands at the peak of climate attacks. The land, water, and weather are being enormously affected by this outbreak of climatic changes. The dangers will intensify, if the precautionary measure is not taken immediately. However, to offset the grave concerns of unintended climatic changes in Bangladesh, there is no any significant initiative is taken. The changes will put its adverse impact on the socio- economic conditions of the country, putting the next generation on the line. Some ominous signs are already there for the concerned to respond with the required amount of fervor. JEL Classification Code: F64